Folliculin (FLCN) in Thyroid Tumors: Incidence, Significance, and Role as a Driver Gene and Secondary Alteration - Faisal A. Hassan; Camryn Slone; Robert J. McDonald; Julie C. Dueber; Adeel M. Ashraf; Melina J. Windon; Oliver J. Fackelmayer; Cortney Y. Lee; Therese J. Bocklage; Derek B. Allison (Current Oncology)
Thyroid carcinomas are driven by diverse molecular alterations, but the tumor suppressor gene folliculin (FLCN), best known for its role in Birt–Hogg–Dubé (BHD) syndrome, has received limited attention in thyroid tumors. Here, we describe two thyroid tumors with pathogenic FLCN alterations—one germline and one somatic—and analyze the broader prevalence and significance of FLCN in thyroid carcinomas using multiple large sequencing datasets, including ORIEN-AVATAR. Patient 1, with a germline FLCN mutation and a history of BHD syndrome, presented with a well-circumscribed oncocytic adenoma. Molecular testing confirmed biallelic FLCN inactivation, but no additional mutations or aggressive features were observed, and the patient remained disease-free post-thyroidectomy. Patient 2 harbored a somatic FLCN mutation in an oncocytic poorly differentiated thyroid carcinoma, which exhibited extensive angioinvasion, high proliferative activity, and concurrent TP53 and RB1 mutations. The tumor progressed with metastatic disease despite multimodal treatment. Thyroid carcinomas revealed FLCN alterations in 1.1% of cases. Pathogenic mutations were rare but associated with oncocytic morphology, while homozygous deletions occurred more frequently in genomically unstable tumors, including anaplastic thyroid carcinoma. These findings suggest FLCN mutations may act as early oncogenic drivers in oncocytic thyroid neoplasms, while deletions represent secondary events in aggressive tumor evolution. The lack of FLCN coverage in standard thyroid molecular panels likely underestimates its clinical relevance. Including FLCN in genetic testing could improve tumor detection and characterization, particularly in BHD patients who may benefit from routine thyroid screening. Further studies are needed to clarify FLCN’s role in thyroid cancer pathogenesis.